2021
DOI: 10.5334/bc.111
|View full text |Cite
|
Sign up to set email alerts
|

Climate change projections for sustainable and healthy cities

Abstract: H. (2021). Climate change projections for sustainable and healthy cities. Buildings and Cities, 2(1), pp. 812-836.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…In fact, CWS increase the potential for improved geographical coverage of observations in cities, rather than only relying on established official meteorological stations, which are often lacking in numbers within cities and therefore in representation of urban climate features (Oke 2004, Grimmond 2006, Muller et al 2013. Densifying CWS networks not only improves our understanding of the urban climate but could further help, for example, intelligent designs of greenspace, street shading and ventilation, surface materials and buildings, and heat adaptation tools (Goodess et al 2021). For instance, the monitoring of locations at higher chances of heat stress in real-time using CWS data (Varentsov et al 2020) illustrates the range of applications offered by CWS.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, CWS increase the potential for improved geographical coverage of observations in cities, rather than only relying on established official meteorological stations, which are often lacking in numbers within cities and therefore in representation of urban climate features (Oke 2004, Grimmond 2006, Muller et al 2013. Densifying CWS networks not only improves our understanding of the urban climate but could further help, for example, intelligent designs of greenspace, street shading and ventilation, surface materials and buildings, and heat adaptation tools (Goodess et al 2021). For instance, the monitoring of locations at higher chances of heat stress in real-time using CWS data (Varentsov et al 2020) illustrates the range of applications offered by CWS.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the region experiences a warm to hot and wet climate with a mean temperature of 22.9 • C and mean annual rainfall of 1490 mm. The port city covers an area of 546 sq.km with a population of about 335,000 [27]. Western Kenya is a predominantly agroeconomic region, and with a growing population and high population density of 130-150 people/sq.km, the land is experiencing increasing pressure.…”
Section: Kisumu Kenyamentioning
confidence: 99%
“…As population density and urbanization have reached incredible levels, extreme weather events have become more frequent, and approximately 70% of disasters are climaterelated [1,2]. Many studies in recent years have also confirmed this [3][4][5][6]. According to climate projections, a strong temperature-increase trend is expected in the next few decades, with extreme increases in daily temperatures, longer hot periods, and more intense heatwaves [5,7].…”
Section: Introductionmentioning
confidence: 99%